2021
DOI: 10.3389/fendo.2020.581878
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analyses of Genes Associated With Osteoporosis in CD16+ Monocyte

Abstract: BackgroundOsteoporosis is a metabolic bone disease characterized by decreased bone mineral density and abnormal bone quality. Monocytes can secret cytokines for bone resorption, resulting in bone mass loss. However, the mechanism by which monocytes subpopulations lead to osteoporosis remains unclear. The aim of this study was to identify genes associated with osteoporosis in monocytes subsets.MethodsThree microarray datasets including GSE7158 (transcription of low/high-peak bone mass), GSE101489 (transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In the present study, we screened and evaluated the role of miR-669g in the modulation of central TPH2 expression, 5-HT depletion, and normal behavioral phenotypes. To screen and evaluate the candidate miRNAs targeting TPH2, we utilized bioinformatics databases (TargetScan, miRDB, and miRanda) to explore miRNA-Tph2 interactions based on both biological experiments and computational-based systems [30,31]. In this study, we employed a combination of three prediction algorithms to identify 15 miRNAs that target the Tph2 3'UTR.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we screened and evaluated the role of miR-669g in the modulation of central TPH2 expression, 5-HT depletion, and normal behavioral phenotypes. To screen and evaluate the candidate miRNAs targeting TPH2, we utilized bioinformatics databases (TargetScan, miRDB, and miRanda) to explore miRNA-Tph2 interactions based on both biological experiments and computational-based systems [30,31]. In this study, we employed a combination of three prediction algorithms to identify 15 miRNAs that target the Tph2 3'UTR.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays much attention is paid to the issues of bone mineral density in children. The results of a number of studies show that about 70-80% of the variability in bone mineral density in a population is determined by genetic factors [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, substantial evidence has shown that the calcification paradox involves multiple biological factors in the bone-vascular axis, including hormones, cytokines, ectoenzymes, inflammatory factors and exosomes (6,7). A chronic inflammatory state contributes to the pathogenesis of both osteoporosis and atherosclerosis, in which circulating monocytes may act as a common trigger and cause unbalanced ectopic calcification (8)(9)(10). It remains unclear whether monocytes serve as a common trigger disturbing the cell state transition in the osteoblast and vascular SMC lineages, and the mechanism underlying unbalanced cross-tissue calcification has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%